Pengaruh Brand Image, Kualitas produk, serta Label Halal terhadap Keputusan Pembelian skincare korea “Some by Mi” pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara - Widya Pangestika; Yenni Samri Julianti Nasution; Rahmat Daim Harahap (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to determine the effect of halal label, brand image and quality on purchasing decisions of Skincare some by mi cosmetics on students of faculty economic University Islamic state . The sampling technique used the Slovin formula so that a sample of 92 people was obtained. This research uses quantitative method. The results showed. 1. The halal label variable partially had a positive and significant effect on purchasing decisions, 2. The brand image variable partially has a significant effect on purchasing decisions. 3. The quality of product variable partially has a significant effect on purchasing decisions. Halal label, brand image and price contributed 86.0% influence to purchasing decisions while the remaining 14.0% was explained by other factors not included in this study.